Pollutants and Greenhouse Gases Emissions Produced by Tourism Life Cycle: Possible Solutions to Reduce Emissions and to Introduce Adaptation Measures - Serrano-Bernardo, Francisco A.; Bruzzi, Luigi; Toscano, Enrique H.; Rosúa-Campos, José L. (IntechOpen, 2012)
None